STRATEGIES FOR FACIAL NERVE PROTECTION DURING PAROTID GLAND SURGERY, A PROSPECTIVE STUDY: USING THE TRAGAL POINTER, POSTERIOR BELLY OF DIGASTRIC AND MASTOID TIP AS LANDMARKS FOR FACIAL NERVE TRUNK IDENTIFICATION IN PAROTID SURGERY. - Roy, Dr Dipayan; Gaurav, Dr Kumar; Nayak, Dr Gajendra; Khan, Dr Zahid M (Student’s Journal of Health Research Africa, 2023)
Background: In order to decrease the likelihood of facial nerve paralysis and address postoperative issues, our goal was to share our experience with parotid surgery. Methods: A 2 year research involving 40 patients with parotid edoema was conducted. Prior to the procedure, a cautious clinical assessment, an examination of the patient’s medical history, and a facial nerve evaluation were carried out. These 40 patients (24 men and 16 women) who had parotid edoema underwent parotidectomy using techniques for an antegrade strategy over a period of two years. Results: Each of the 40 patients had a superficial parotidectomy. Thirteen patients (32.5%) exhibited impairments in facial loss of nerve mobility, with seven having HB II (17.5%), four having HB Scale III (10%), and six having HB IV (15%). The majority of patients (18/30 patients) in this study showed significant recovery between four to six months following the procedure of surgery (mean time for recovery: 7 months), and patients affected had recovered in the time duration of 11 months of parotidectomy. Conclusion: To reduce the likelihood of transient facial nerve paresis, the following safety measures were used in this investigation “vertical retraction” to lower the possibility of traction injuries. Bipolar diathermy was performed after the nerve trunk was located, and surgical sutures (5/0 polyglactin) were used to create hemostasis. With a sensitivity of 67% and a specificity of 13%, FNAC remains the investigation of choice. The numerical outcomes of the many parameters that were evaluated show that they are consistent with research from previous studies and the medical literature. Recommendation: The techniques discussed in the study if employed can significantly reduce the risk of facial nerve dysfunction. Thus, while performing Parotid gland surgery the technique should be employed.